PENGARUH PEMBELAJARAN PROBLEM SOLVING BERORIENTASI HOTS (HIGHER ORDER THINKING SKILLS) TERHADAP HASIL BELAJAR KIMIA SISWA KELAS X - Handayani, Ririn; Priatmoko, Sigit (Jurnal Inovasi Pendidikan Kimia, 2013)
This study aimed to determine the effect of problem solving learning with HOTS (Higher Order Thinking Skills) oriented on the results of class X students of chemistry subject on the concept of electrolyte solution and redox. The population are 286 high school students of class X in Semarang. Sampling is done by cluster random sampling technique, one was selected as the experimental class and one as a control class. The average value of cognitive learning outcomes  1051  for experimental class 84.06, while the control class 77.60. Both classes are normally distributed and have the same variance, whereas the t test of the two-part generated -t table (-2.00)<t count (4.32)>t table (2.00) which means there is a significant difference between the two classes. On the right side of the t test obtained t count (4,32)>t table (1,67) which means that the average student's cognitive learning outcomes experimental class was better than the control class. The results of the correlation analysis obtained r=0.5079, so it was significant with coefficient of determination of 25.79%, which means the use of problem solving learning with HOTS oriented has contribution 25.79% on the student learning outcomes, whereas 74.21% is explained by other variables. It can be concluded that the use of problem solving learning with HOTS oriented have positive effect on students' learning outcomes. Problem solving learning can stimulate students' higher order thinking skills such as critical and creative thinking.